Exploring the medicinal significance of l-Arginine mediated nitric oxide in preventing health disorders - Mega Obukohwo Oyovwi; Adedeji David Atere (European Journal of Medicinal Chemistry Reports)
l-Arginine is an essential amino acid that plays a crucial role in various physiological processes. It serves as a precursor for nitric oxide (NO), which has potent antioxidant and anti-inflammatory properties. This review aims to comprehensively examine the medicinal importance of l-arginine as a natural antioxidant in preventing human health disorders. A comprehensive literature search was conducted using PubMed, Google Scholar, and other databases. Studies investigating the antioxidant effects of l-arginine and its potential role in preventing various diseases were included. l-Arginine has been shown to mediate NO production with strong antioxidant properties, scavenging free radicals and reducing oxidative stress. It has demonstrated therapeutic potential in preventing and mitigating various health conditions, including: Cardiovascular diseases, Neurodegenerative diseases, Metabolic disorders, Immune function and Anti-aging effects. l-Arginine is a potent natural antioxidant with significant medicinal importance. Its ability to scavenge free radicals, improve endothelial function, and support immune function makes it a promising therapeutic agent for preventing and treating a wide range of human health disorders. Further research is warranted to fully elucidate the mechanisms of action and optimal dosage for specific conditions.